Effects of Consuming Pulsed UV Light-Treated Pleurotus citrinopileatus on Vitamin D Nutritional Status in Healthy Adults - Chih-Ching Hsu; Chiao-Ming Chen; Yu-Ming Ju; Yu-Ching Wu; Huei-Mei Hsieh; Shu-Hui Yang; Chien-Tien Su; Te-Chao Fang; Widiastuti Setyaningsih; Sing-Chung Li (Foods)
Vitamin D, essential for growth and health, is often deficient in Taiwan despite abundant sunlight. Plant-derived vitamin D2 (ergocalciferol) is bioavailable, environmentally friendly, and cost-effective. This study evaluated the efficacy of enhancing Pleurotus citrinopileatus (PC) mushrooms’ vitamin D2 content through pulsed ultraviolet (PUV) light and its impact on vitamin D status in humans. In a four-week randomized parallel trial, 36 healthy participants were assigned to three groups: a control group, a group consuming 10 g/day PUV-treated PC (PC-10 g), and a group consuming 100 g/day PUV-treated PC (PC-100 g). Blood samples collected pre- and post-intervention measured serum 25(OH)D2, 25(OH)D3, and biochemical parameters. After four weeks, serum 25(OH)D2 levels significantly increased in the PC-10 g group (1.47 ± 1.42 ng/mL to 9.50 ± 7.10 ng/mL, p = 0.001) and in the PC-100 g group (1.94 ± 2.15 ng/mL to 21.82 ± 16.75 ng/mL, p = 0.002), showing a 10.2-fold rise. The PC-100 g group also experienced a 37.6% reduction in serum intact parathyroid hormone (I-PTH) levels (26.26 ± 9.84 pg/mL to 16.38 ± 5.53 pg/mL). No adverse effects were reported. PUV-treated PC mushrooms significantly increase serum 25(OH)D2 levels and reduce I-PTH, particularly at higher doses. These findings underscore the potential of vitamin-D-enriched PC as a sustainable, fungi-derived food source for addressing vitamin D deficiency.